The role of sex‐related voice variation in children's gender‐role stereotype attributions. (20th March 2019) - Cartei, Valentina; Banerjee, Robin; Hardouin, Loïc; Reby, David
Abstract : In the absence of clear sex differences in vocal anatomy, the expression of gender in pre‐pubertal children's voices has a strong behavioural dimension. However, whether children are sensitive to this gender‐related variation in the voice and use it to make inferences about their peers' masculinity and femininity remains unexplored. Using a cross‐modal matching task, thirty‐one 7‐ to 8‐year‐olds and forty‐two adults were asked to associate prototypical voices of boys and girls, and their re‐synthesized masculinized and feminized versions, to fictional stereotypically masculine, gender‐neutral, and stereotypically feminine child characters. We found that listeners spontaneously associated stereotypically masculine and feminine descriptors of a child character with masculinized voices and feminized voices, respectively. Adults made overall more stereotypical associations and were less influenced by character sex than children. Our observations highlight for the first time the contribution of acoustic cues to gender stereotyping from childhood, and its potential implications for the gender schema literature. Statement of contribution What is already known on this subject? Research on stereotyping shows children's schematic processing of the visible aspects of gender expression Psychoacoustic research shows that variation in children's voices affects adults' judgments of their masculinity What does this study add? Children and adults linked voice variation to gender‐stereotypical characterizations of child characters Adults made overall more stereotypical associations than children and were less influenced by character's sex Our results highlight the existence of a vocal component in children's and adults' gender schemas